2017
DOI: 10.1088/1361-6528/aa81e1
|View full text |Cite
|
Sign up to set email alerts
|

Plasmonic enhancement of cyanine dyes for near-infrared light-triggered photodynamic/photothermal therapy and fluorescent imaging

Abstract: Near-infrared (NIR) triggered cyanine dyes have attracted considerable attention in multimodal tumor theranostics. However, NIR cyanine dyes used in tumor treatment often suffer from low fluorescence intensity and weak singlet oxygen generation efficiency, resulting in inadequate diagnostic and therapy efficacy for tumors. It is still a great challenge to improve both the photodynamic therapy (PDT) and fluorescent imaging (FLI) efficacy of cyanine dyes in tumor applications. Herein, a novel multifunctional nan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 21 publications
(13 citation statements)
references
References 50 publications
0
12
0
1
Order By: Relevance
“…If we limit ourselves to experiments that investigate possible plasmonic effects on the production and removal of O 2 (a 1 Δ g ), the list is still remarkably long. 16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]38 (The references cited represent only a fraction of the published literature.) In looking at many of these latter studies, we find reported enhancement factors that fall in the range of ∼0.5−2.0.…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 99%
“…If we limit ourselves to experiments that investigate possible plasmonic effects on the production and removal of O 2 (a 1 Δ g ), the list is still remarkably long. 16,[18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35]38 (The references cited represent only a fraction of the published literature.) In looking at many of these latter studies, we find reported enhancement factors that fall in the range of ∼0.5−2.0.…”
Section: The Journal Of Physical Chemistry Cmentioning
confidence: 99%
“…Although the PTT and PDT of heptamethine and the derivatives as photosensitizers have potential for cancer therapy, any single phototherapy modality has limitations in large and deep vivo tumor therapy according to clinical observation due to the significant therapeutic effects decreasing over time (Luo et al, 2016;Lu et al, 2017;Cao et al, 2019;Xue et al, 2019). Compared with conventional single therapy, multimodal therapies integrating PDT and PTT, have been more widely applied in tumor treatment because they hybrid the merits of light-guided therapy, exhibiting relatively low toxicity, negligible metastasis, recurrence of tumor, and significantly improving the therapeutic effect (Luo et al, 2016;Lu et al, 2017;Xue et al, 2019). In vivo and in vitro safety assessment showed the low cytotoxicity of CyI.…”
Section: Photothermal Therapy and Photodynamic Therapymentioning
confidence: 99%
“…Such complexity was best exemplified by Au-based nanomaterials with various morphology, e.g., Au nanorods, Au nanostars, Au nanoclusters. In these conjugates, cyanine fluorophores could be covalently conjugated to Au nanomaterials via Au–S bond [ 61 , 62 ], or indirectly modified through polymer coating [ 63 ], complementary base pairing [ 64 ] etc. ; and many conjugates also exhibited off-on fluorescence/PDT response towards internal stimuli such as pH, GSH, cathepsin E and matrix metalloproteinases (MMPs).…”
Section: Phototherapymentioning
confidence: 99%